The beneficial effects of temperature on antioxidant and Anti-inflammatory potential of trichosanthesdioica Leaf extract (Funded Work) - SWATI BANERJEE; KAMALA ADAK (International Journal of Pharma and Bio Sciences, 2017)
The medicinal plant provides remedies of many diseases due to their phytochemicals content. The objective of the present study is to focus on the stability of phytochemicals of Trichosanthes dioica leaf extract under wide range of temperature (100ºc, 150ºc 180ºc) applied for different time variation (10, 20, 30 min). The variation of phytochemicals (Polyphenol and Flavonoid), and in vitro antioxidant capacity (DPPH, ABTS, OH radical scavenging assay, Ferric reducing ability potential, total antioxidant capacity) and anti-inflammatory activity (inhibition of albumin denaturation assay) of the sample (methanolic leaf exract) with temperature are studied. Result suggests that the raw (without temperature effect) leaf extract of sample is good in phytochemicals content (182.87±1.51 mg/g polyphenol and 210.96±8.01mg/g flavonoid content) as well as free radical scavenging potential. Its potentiality in term of antioxidant activity increases with temperature and observed to be maximum at 180ºC (polyphenol content- 259.61g±18.78 mg/g and flavonoid content-269.68h±7.82mg/g) but less time period (10 to 20 min) is suggested to be optimum. So, It may be concluded that the phytochemicals content which are responsible for antioxidant potential, increases with temperature which suggests its uses as green leafy vegetables in daily dining as well as in pharmaceutical industry for drug discovery.